The Ecological Scarcity Method for the European Union: A Volkswagen Research Initiative: Environmental Assessments - Ahbe, Stephan (AutoUni - Schriftenreihe, 2017)
environmental impact; environmental assessment; ecological scarcity; energy management; European Union; Volkswagen Research